The influence of implementation work-based learning model on learning innovation skills student’s - Negara, Irma Manda; Hidayati, Nurul (Universitas Negeri Padang, 2020)
This study aimed to analyze the influence of internship as a form of the WBL model to LIS students, in terms of the assessment theory of work-based learning and framework of 21st-century skills. The method used is descriptive quantitative, with respondents students who have done internships. The results showed that there are significant WBL (X) on critical thinking and problem-solving skills (Y1), indicated by the results of the significance value 0.000 <0.050 probability and the value of t, the obtained value of tcount 6.177 > ttable 2.024. Next, there is the influence of WBL (X) on communication skills (Y2), seen from the significance value of 0.000 <0.050 probability. Then, for a value of t, obtained the value of tcount 5,039> ttable 2,024. There is the influence of WBL (X) on collaboration skills (Y3), seen at a significance value of 0.000 <0.050 probability. Then, for a value of t, the obtained value of tcount 5,405 > ttable 2,024. There is no significant and positive relationship between the implementation of WBL and students' Creativity and Innovation skills (Y4). This can be seen when the linearity test is carried out. The implementation of an internship can contribute to the development of skills covered in LIS, except for creativity and innovation skills.